DOG EAT DOG / JUST JAKE - Jake Marcionette; Rivas, Victor (New York: Grosset & Dunlap, an imprint of Penguin Group (USA) LLC, 2015)
Sixth-grader Jake Ali Mathews is slowly settling in at his new school and has a new best friend, Michael, but a substitute teacher arrives who instructs by having her students help with a fledgling pet-grooming company, which strains his friendship and tests his growing popularity.
JUNIOR
Keywords: Middle schools -- Fiction; Schools -- Fiction; Popularity -- Fiction; Friendship -- Fiction; Substitute teachers -- Fiction; Pet grooming salons -- Fiction; Brothers and sisters -- Fiction; Humorous stories; JUVENILE FICTION / Social Issues / Friendship; JUVENILE FICTION / Family / Siblings; JUVENILE FICTION / Social Issues / Bullying